Non-Pharmacological Interventions for Pain Management in Palliative Care Patients: A Literature Review - Desi Fitriyanti; Nurul Huda; Erika Erika (Indonesian Journal of Global Health Research, 2026)
Pain is one of the most prevalent symptoms experienced by palliative care patients and significantly affects their quality of life. Although various interventions have been developed, pain management remains suboptimal, particularly regarding the implementation of evidence-based non-pharmacological interventions. Therefore, a literature synthesis is needed to identify effective and practical interventions for palliative nursing care. This study aimed to identify non-pharmacological interventions for pain management in palliative care patients. This study employed a Narrative Literature Review design guided by the PRISMA framework. Articles were searched through PubMed, ScienceDirect, and Google Scholar databases, covering publications from 2020 to 2026. The inclusion criteria included randomized controlled trials (RCTs) and quasi-experimental studies investigating the use of non-pharmacological interventions for pain management in palliative care patients. Article selection was conducted through identification, screening, and eligibility assessment stages. The data were analyzed descriptively using a narrative synthesis approach. A total of six articles meeting the inclusion criteria. The findings indicated that non-pharmacological interventions, including Progressive Muscle Relaxation (PMR), massage therapy, hot and cold compresses, and movement-based relaxation therapy, were effective in reducing pain intensity and improving the quality of life of palliative care patients. PMR demonstrated the most consistent effectiveness in reducing pain while improving sleep quality and daily functioning. Massage therapy and compress interventions also provided additional benefits by enhancing patient comfort. Non-pharmacological interventions are effective in managing pain among palliative care patients. A multimodal approach integrating both physical and psychological aspects is strongly recommended in nursing practice. PMR may be considered a primary intervention due to its effectiveness, ease of implementation, and ability to support patients' self-management of pain over the long term.